Plantago major Linne 1753 - Hassemer, Gustavo (Zenodo, 2017)
Plantago major Linné (1753: 112–113) Type: —COUNTRY UNKNOWN. S.d. (lectotype [designated by Verdcourt 1971: 2] LINN-144.1!). Image of the lectotype available at: http://linnean-online.org/8760. Description: —Rosette herbs, perennial, but effectively behaving as annual in warmer climates. Taproot almost always absent, substituted with numerous unthickened (to 1.5 mm wide) cord-like secondary roots; if a taproot is present, it is unthickened. Caudex generally inconspicuous, to 3 cm long, without a conspicuous tuft of reddish trichomes at its apex. Leaves ovate, with a very evident petiole, membranaceous to papiraceous, glabrous to pilose. Trichomes on leaves and scapes ribbon-shaped, compressed, perceptibly gradually tapering towards the apex (types G, H and I); those on scapes antrorse, appressed. Spike multiflowered, with flowers densely packed throughout the entire length of the spike. Corolla actinomorphic, glabrous, becoming rather inconspicuous after fruit maturation. Stamens 4. Pyxidia 6–31-seeded. Seeds very variable, irregularly angled; surface rugose. Illustrations: —Fig. on page 8 in Bassett (1973); Fig. 149 in Cabrera (1993); Fig. 4L–V in Hefler et al. (2011). Distribution: —Originally native to Europe, North Africa and western and central Asia, this species was spread by man and became naturalised in most of the world, occurring today on every continent except Antarctica (Rahn 1996, Samuelsen 2000, Hefler et al. 2011). This is by far the commonest and widest-distributed species of Plantago , globally and also in Brazil. In this country, P.major was hitherto recorded in the following states: Acre, Bahia, Ceará, Distrito Federal, Espírito Santo, Goiás, Minas Gerais, Mato Grosso do Sul, Pará, Paraíba, Pernambuco, Paraná, Rio de Janeiro, Rio Grande do Norte, Rio Grande do Sul, Santa Catarina and São Paulo (Souza 2010, Souza & Hassemer 2015). Here I present the first records of this species in Mato Grosso, where it has been collected in four municipalities: Comodoro, Poxoréu, Tangará da Serra and Vila ...